Case of multiple sclerosis presenting as unilateral internuclear ophthalmoplegia - Aishwarya M Angadi (Kerala Journal of Ophthalmology, 2022)
A 30-year-old female presented with complaints of decreased vision and diplopia since 1 week along with headache and gait disturbances. Examination revealed medial restriction of ocular movements in the right with left abducting nystagmus suggestive of right-sided internuclear ophthalmoplegia and right-sided facial palsy. The patient was admitted under neurology as a suspected case of demyelinating disorder. Magnetic resonance imaging with gadolinium contrast revealed features suggestive of probably multiple sclerosis (MS). The patient was given 5 days of high-dose intravenous steroids following which the patient showed improvement and was discharged on multivitamins. Subsequent follow-up showed significant improvement in symptoms, visual acuity, and ocular movements. Hereby presenting a rare case of MS presenting as unilateral internuclear ophthalmoplegia.